(untitled) (Universal International Scientific Journal, 2026)
This article studies the effect of the harmful weevil (Eurygaster integriceps Put) on the germination and germination capacity of seeds of 20 varieties of soft wheat zoned in the Republic and 23 varieties of Kazakhstani selection. When analyzing the germination, germination and germination capacity indicators of the damaged wheat grains, it was found that the harmful weevil had a significant impact. As a result, it was observed that the germination indicators and germination capacity of the studied varieties were less than 50%.